Host Range Mutants of Polyoma Virus - Benjamin, Thomas L. (1970)
A line of polyoma-transformed mouse cells has been isolated which is fully susceptible to lytic infection by polyoma virus. This line has been used to select virus mutants which have lost most or all of their ability to grow in the untransformed parental line while retaining the ability to grow in the transformed derivative. These virus mutants are also defective in their ability to transform cells of rat or hamster origin. Since the DNA extracted from the mutants has the same host range as the whole virus, the mutants appear to be blocked at some intracellular step which is required both for the completion of virus development in mouse cells and for transformation in rat or hamster cells.